A Pilot Survey of Awareness and Knowledge of Human Papillomavirus (HPV), Cervical Cancer and HPV Vaccine among Men and Women Attending for HPV Vaccination in Terengganu, Malaysia - Shabbir Ahmad, Sheikh; Husbani, Mohd Amin Rebuan; Nor Iza, A.Rahman (2015)
Cervical cancer is a major public health problem and it is the leading cause of cancer-related deaths in women as reported. The primary underlying cause of cervical cancer is human papilloma virus (HPV) which is the most common sexually transmitted infection. A little is known about the awareness and knowledge of HPV infection, cervical cancer and HPV vaccine in Malaysian women and men. Therefore, this survey is aimed to assess. A cross-sectional survey study was conducted at Universiti Sultan Zainal Abidin, Terengganu, Malaysia using a self-administered, anonymous questionnaire. A total of 112 women and men aged 15-45 years were included who came for HPV vaccination. Data were analysed with SPSS version 16.0 using standard descriptive statistic and P-values < 0.05 were considered significant. Mean age of respondents was 30 years. Overall, 99% of respondents knew that HPV vaccine protects them from cervical cancer, however, 68% were not aware of its effectiveness; 73% knew that HPV vaccine will not replace Pap smear screening; 94% correctly reported that HPV vaccine is also beneficial for males; 85% knew that HPV vaccine is not safe in pregnancy; Only 45% knew that HPV vaccine can be given during breast feeding; 77% respondents were motivated for vaccination through doctors; interestingly, 70% accepted that the cost of HPV vaccine is within acceptable price range. Study assessed knowledge about HPV infection and its vaccine. Results are encouraging. However, aggressive education is necessary to increase awareness and knowledge of HPV infection and its vaccine.